Laudivius Zacchia’s 'Epistolae Magni Turci' in two Spanish Early Printed Books: New data for identification - Domingo Malvadi, Arantxa (Revista General de Información y Documentación, 2020)
Laudivio Zacchia’s Epistolae Magni Turci, for a long time attributed to Mehmet II, were destined to become a bestseller in the Early printing Europe with about twenty editions between 1473 and 1500. Two Spanish editions were known until now: one, unsigned, was attributed to Paul Hurus’ workshop in Zaragoza circa 1480-1484; the other, dated in 1490, to Botel’s workshop in Lérida. A third unknown edition of the work, not mentioned in the bibliographical repertoires, is now identified and attributed also to Hurus’ workshop. A new assessment is made of the available information on the Spanish first editions of this work and their preserved copies.
Keywords: Zacchia; Mehmed II; early printed books; Spanish incunabula; printing history; book history; Paul Hurus; Zaragoza; Barcelona; Naples; Rhodes; Mediterranean